2022
DOI: 10.1177/19322968221093078
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth Technologies in Diabetes Self-management and Education

Abstract: Background: The coronavirus pandemic of 2019 (COVID-19) forced worldwide recognition and implementation of telehealth as a means of providing continuity of care by varied health care institutions. Diabetes is a global health threat with rates that continue to accelerate, thereby causing an increased need for clinicians to provide diabetes care and education to keep up with demand. Utilizing technology to provide education via phone/smartphone, video/audio, web, text message, mobile apps, or a combination of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 87 publications
(173 reference statements)
1
4
0
Order By: Relevance
“…A drawback of the telehealth videoconferencing modality mentioned by some participants was the absence of the "human touch" one would often have with a clinician during an in-person consultation. These sentiments are similar to those reported in a previous study examining the advantages and disadvantages of telehealth technology in diabetes education [42]. The benefits of telehealth technology still outweigh the limitations, as virtual video platforms were accepted among participants of various ages in our study.…”
Section: Telehealth Usabilitysupporting
confidence: 90%
“…A drawback of the telehealth videoconferencing modality mentioned by some participants was the absence of the "human touch" one would often have with a clinician during an in-person consultation. These sentiments are similar to those reported in a previous study examining the advantages and disadvantages of telehealth technology in diabetes education [42]. The benefits of telehealth technology still outweigh the limitations, as virtual video platforms were accepted among participants of various ages in our study.…”
Section: Telehealth Usabilitysupporting
confidence: 90%
“…Therefore, it leads to greater accessibility for rural and underserved populations. 38 Lastly, technological advancement permits the measurement of multiple glucose metabolism indicators, enabling more accurate control of glucose metabolism and potentially improving the management of diabetes. 39 Our findings revealed that there was no significant difference in glycosylated haemoglobin (HbA1c) levels between the intervention and usual care groups, which is a finding consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also found that telehealth education and counseling could enhance glycemic control. 29 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…This is in line with other studies that found that telehealth educational intervention helped to improve glycemic control, improve self-management, and reduce risk factors. 29 , 30 …”
Section: Discussionmentioning
confidence: 99%